Integrating Digital Twin Technology to Achieve Higher Operational Efficiency and Sustainability in Manufacturing Systems - Matevž Resman; Niko Herakovič; Mihael Debevec (Systems)
Digital twin technology has proven to be a transformative tool in the development of smart factories by providing real-time data-driven simulations and virtual representations of physical assets and systems. This paper explores the integration of digital twins in the context of Industry 4.0 and sustainability, highlighting their potential to increase operational efficiency, optimize material usage and minimize waste. To demonstrate these benefits, case studies are presented in which a digital twin of a real manufacturing system was implemented. The digital twin enabled us to run different “what-if” scenarios to evaluate the improvements in the manufacturing system, efficiency and reduction of raw material consumption and waste by incorporating quality control operations at all assembly stations. Based on the analyzed results of both case studies, we demonstrated that additional quality control operations had a significant impact on the efficiency of the manufacturing system and its sustainability, as waste was significantly reduced. The proposed approach has proven to be highly effective for different types and sizes of manufacturing systems, especially those with high waste generation.